Figment Authentication Scheme in Wireless Sensor Network - Ambika, N.; Raju, G. T. (Security Technology, Disaster Recovery and Business Continuity, 2010)
Sensor nodes are of low-cost and hence vulnerable to attacks. The adversaries need not endure hardship to control these nodes. Malicious nodes or compromised nodes are difficult to detect. These malicious nodes drain the energy available, give false readings, project itself to be as one of the routers hence attracting all the packets leading to denial of service attack. This paper is trying to test the nodes for its fidelity by considering one of the normal procedures to initiate action among the normal nodes. The paper utilizes public key cryptographic methods and TDMA technology to accomplish the task.